Blockchain in Emission Management: Opportunities and Trends - Ali, Tagreed (2023)
The emergence of blockchain technology in different use cases is remarkable. Blockchain has the potential of transforming global business, particularly in the field of emission management. The unique features of blockchain technology encouraged scholars and startups to invest in utilizing blockchain within emission management, however, there is a need to review the literature related to blockchain and its potential to advance emission management and climate change. Hence, this paper provides an overview of the current trends as well as future opportunities that can be pursued in this space.